Benefits of Corporate Social Responsibility (CSR) for the Community of Mundu Village, Klaten - Setiawati, Diana; Febriani, Hanifah; Wibowo, Rio Pradita; Anggraeni, Chintya (Universitas Muhammadiyah Magelang, 2025)
This community service activity aims to provide an understanding of the benefits of the Corporate Social Responsibility (CSR) program for improving the welfare of the community in Mundu Village, Klaten Regency. CSR is understood as a company's social responsibility that is not only oriented towards economic profit, but also towards sustainable social and environmental contributions. The implementation methods included field observations, interviews with village officials and beneficiary communities, and focus group discussions (FGDs). The results of the activity showed that the CSR program in Mundu Village had a positive impact on the economy through the empowerment of MSMEs and skills training, on society through the improvement of public facilities and education, and on the environment through waste management based on waste banks and the use of cow dung waste to produce biogas.